(AlCrMg)x(PO4)y/MgO composite: A new thermal protection and insulation material up to 2400 °C. (October 2022) - Zhan, Zizhang; Sun, Wei; Zhang, Shuaishuai; Wen, Qingbo; Zhang, Hongbo; Xiong, Xiang
Abstract: A (AlCrMg)x (PO4 )y /MgO composite(APMC) was prepared based on the acid–base reaction between MgO and chromium aluminum phosphate solution for thermal protection and insulation applications at ultrahigh-temperatures up to 2400 °C. The compositions, formation mechanisms, microstructure, mechanical properties, thermal conductivity and ablation resistance of the composite were systematically investigated. The results show that the (AlCrMg)x (PO4 )y /MgO composite can be consolidated in different shapes at room temperature. The compressive strength of the as-prepared porous composites is higher than 20 MPa due to the macromolecular network structure, and it can be further improved to 42 MPa via thermal treatment. After ablation by an oxyacetylene flame at 2400 ± 70 °C for 60 s, the mass and line ablation rates of the composite were 0.0195 g/s and 0.43 × 10 −3  mm/s, respectively, which are comparable to those of ultrahigh-temperature ceramics. The excellent ablation resistance can be attributed to the in situ formation of a dense protective layer composed of spinel MgCr2 O4 and MgO phases. Interestingly, during ablation at 2400 °C the back-side temperature of the 15 mm-thick sample was lower than 130 °C, suggesting outstanding thermal insulation performance. The temperature gradient leads to the formation of a gradated porous structure which reduces the overall thermal conductivity of the composite. Graphical abstract: Image 1 Highlights: A (AlCrMg)x(PO4)y/MgO composite (APMC) is first developed as an ultra-high temperature resistant thermal insulation material. The APMC based on macromolecular network structure has high strength. The APMC has excellent ablation resistance. The gradient pore structure enables APMC suggesting outstanding thermal insulation performance.